Biometallic ions and derivatives: a new direction for cancer immunotherapy - Lin Zhao; Yajun Gui; Jing Cai; Xiangying Deng (Molecular Cancer)
Abstract Biometallic ions play a crucial role in regulating the immune system. In recent years, cancer immunotherapy has become a breakthrough in cancer treatment, achieving good efficacy in a wide range of cancers with its specificity and durability advantages. However, existing therapies still face challenges, such as immune tolerance and immune escape. Biometallic ions (e.g. zinc, copper, magnesium, manganese, etc.) can assist in enhancing the efficacy of immunotherapy through the activation of immune cells, enhancement of tumor antigen presentation, and improvement of the tumor microenvironment. In addition, biometallic ions and derivatives can directly inhibit tumor cell progression and offer the possibility of effectively overcoming the limitations of current cancer immunotherapy by promoting immune responses and reducing immunosuppressive signals. This review explores the role and potential application prospects of biometallic ions in cancer immunotherapy, providing new ideas for future clinical application of metal ions as part of cancer immunotherapy and helping to guide the development of more effective and safe therapeutic regimens.